TRANSFORMASI PERENCANAAN PEMBELAJARAN PAI DIGITAL: DARI KONSEP MENUJU IMPLEMENTASI NYATA - Firda Ayu Kumala; Siti Mutammimah; Aisyati Eka Pratiwi; Devy Habibi Muhammad (AL Fikrah: Jurnal Pemikiran dan Pendidikan Islam, 2026)
This study aims to analyze the transformation of Islamic Religious Education (PAI) instructional planning in the digital era, moving from conceptual frameworks to contextual and applicable actions. Although theoretically designed to develop character and contextual Islamic values, the reality in the field shows that PAI lesson planning is still dominated by normative and administrative practices. This study highlights the need to reframe planning as a strategic process that integrates technology, participatory pedagogical approaches, and Islamic values that align with modern life. A qualitative approach with a library research method was employed, analyzing various scholarly sources on educational innovation, digitalization, and instructional design. The results reveal that PAI instructional planning transformation can be realized through three core components: technology integration, participatory learning models, and contextual reinforcement of Islamic values. By positioning the teacher as a learning experience designer, instructional planning in PAI can serve as a means to create inspirational, relevant, and transformative learning processes in the digital age.